2017
DOI: 10.1039/c6ra27378e
|View full text |Cite
|
Sign up to set email alerts
|

Ring opening of decalin over bifunctional Ni–W carbide/Al2O3–USY catalysts and monofunctional acid Ni–W oxide/Al2O3–USY

Abstract: The ring opening reaction of decalin was studied over two types of catalyst, including bifunctional catalysts (Ni–W carbide/Al2O3–USY) and monofunctional acid catalysts (Ni–W oxide/Al2O3–USY) with different amounts of metal loading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 56 publications
2
8
0
Order By: Relevance
“…% Ag) are shown in Figure 2. The diffraction lines corresponding to the η-Al2O3 phase decreased with increasing the Ag loading, due to the metal coverage onto the η-Al2O3 support with increasing the silver metal loadings which is in agreement with the work done by Yuan et al 35 36 . It is worth noting that all catalysts showed amorphous structures with broad diffraction peaks.…”
Section: Catalyst Characterisationsupporting
confidence: 91%
See 2 more Smart Citations
“…% Ag) are shown in Figure 2. The diffraction lines corresponding to the η-Al2O3 phase decreased with increasing the Ag loading, due to the metal coverage onto the η-Al2O3 support with increasing the silver metal loadings which is in agreement with the work done by Yuan et al 35 36 . It is worth noting that all catalysts showed amorphous structures with broad diffraction peaks.…”
Section: Catalyst Characterisationsupporting
confidence: 91%
“…The XRD patterns of η-Al 2 O 3 catalyst along with silver modifications at different levels of loadings (1, 10, and 15 wt % Ag) are shown in Figure . The diffraction lines corresponding to the η-Al 2 O 3 phase decreased with increasing Ag loading, due to the metal coverage onto the η-Al 2 O 3 support with increasing the silver metal loadings which is in agreement with the work done by Yuan et al The catalyst 15% Ag/η-Al 2 O 3 with the highest Ag loading showed diffraction lines related to hexagonal Ag 2 O (100) at 2θ = 33.6 and 38.39 Å (JCPDS no. 72-2108) and a minor diffraction line for the metallic silver at 2θ = 77.30 Å (ICDD 76-1393) .…”
Section: Silver Modification η-Al2o3supporting
confidence: 90%
See 1 more Smart Citation
“…Mafokoane et al [36] obtained similar results using Cuo/Al 2 O 3 -WO 3 (6%) as the catalyst, obtaining a higher conversion of LA, but the selectivity of GVL decreased due to the increase in Lewis-type acidity, creating 2-Methyltetrahydrofuran (2-MTHF). Yuan et al [37] reported a 100% ring opening and decalin conversion using Ni-WO 3 /Al 2 O 3 -Zeolite at 345 • C, attributed to abundant strong Brönsted acid sites with an increase in WO 3 loading until reaching the 18% by weight. In addition to the importance of the particle size for the hydrogenation of LA to GVL, the acid-base properties and the structural characteristics of the support represent an important role at the moment of hydrogenation [38].…”
Section: Introductionmentioning
confidence: 99%
“…Bifunctional catalysts are generally used to achieve the selective ring opening (SRO) of six-membered naphthenic molecules. [7][8][9][10][11][12][13][14][15][16] Acid sites catalyze cracking, isomerization and dealkylation, while the metal sites promote de/hydrogenation and hydrogenolysis. 17 Hydrogenolysis of cycloalkanes, especially four and ve-membered rings cycloalkanes, was rst studied in depth on Pt/Al 2 O 3 by François Gault and his collaborators, [18][19][20] who laid the foundation of the reaction mechanisms that are still used by the heterogeneous catalysis community.…”
Section: Introductionmentioning
confidence: 99%